2007
DOI: 10.1096/fj.07-8174com
|View full text |Cite
|
Sign up to set email alerts
|

Lactate sensitive transcription factor network in L6 cells: activation of MCT1 and mitochondrial biogenesis

Abstract: We hypothesized that in addition to serving as a fuel source and gluconeogenic precursor, lactate anion (La-) is a signaling molecule. Therefore, we screened genome-wide responses of L6 cells to elevated (10 and 20 mM) sodium-La- added to buffered, high-glucose media. Lactate increased reactive oxygen species (ROS) production and up-regulated 673 genes, many known to be responsive to ROS and Ca2+. The induction of genes encoding for components of the mitochondrial lactate oxidation complex was confirmed by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
386
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 370 publications
(416 citation statements)
references
References 54 publications
26
386
3
1
Order By: Relevance
“…Previous observations reported the ability of L-lactate to stimulate gene expression in different cell types in culture such as L6 cells, vasculogenic stem cells, mesenchymal stem cells, or fibroblasts although the activation of specific transcription factors (14)(15)(16)(17). In the present study we show that L-lactate induces the expression of key plasticity-related genes, namely, Arc, Zif268, c-Fos, and BDNF in neuronal cultures.…”
Section: Discussionsupporting
confidence: 71%
“…Previous observations reported the ability of L-lactate to stimulate gene expression in different cell types in culture such as L6 cells, vasculogenic stem cells, mesenchymal stem cells, or fibroblasts although the activation of specific transcription factors (14)(15)(16)(17). In the present study we show that L-lactate induces the expression of key plasticity-related genes, namely, Arc, Zif268, c-Fos, and BDNF in neuronal cultures.…”
Section: Discussionsupporting
confidence: 71%
“…We did not measure the MCT4 lactate transporter because MCT4 plays a role in releasing lactate from muscle to other tissues, not uptake into muscle, and has a much higher Km value for lactate compared with MCT1 (32). Hashimoto et al reported that lactate can be a signal to increase MCT1 and mitochondrial protein expression, but not MCT4 (33). In our study, post-exercise lactate administration increased the blood lactate concentration to approximately 5 mmol/L for 2 h. We speculate that the higher lactate concentration is the result of the increased MCT1 protein expression.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, lactate also functions as a reporter. It controls the expression of mitochondrial factors and activates master genes of metabolic regulation, including nuclear respiratory factor-2 and the peroxisome proliferator activated-receptor g coactivator-1a [63].…”
Section: Reviewmentioning
confidence: 99%